Implementation of PTSL (Complete Systematic Land Registration) as Legal Certainty in Securing Land Rights by the Community in Bali - Hartawan, I Kadek Dony; Suyatna, Nyoman; Marwanto, Marwanto; Santosa, A.A.Gede Duwira Hadi (Formosa Journal of Multidisciplinary Research, 2024)
The aim of this research is to determine the implementation of PTSL (Complete Systematic Land Registration) as legal certainty in guaranteeing land rights by the community in Bali. This research is an empirical normative research, namely researching the implementation of land registration for legal certainty through PTSL. The results of this research show that Internal obstacles or barriers faced by the Land Office in implementing PTSL, include: Lack of number of implementing personnel and measuring equipment, Lack of coordination between the Land Office and the Village Office, Lack of counseling provided to the community , especially land rights holders regarding land registration issues. External obstacles or barriers faced by the community such as the requirements shown for completeness in submitting an application for certification through PTSL are incomplete.